Biological age as a basis for determining prenozological states in elementary school-age children. - Omelchenko T.G (Kharkov National Pedagogical University, 2011)
The necessity of determining the biological age (BA) in elementary school-age children as an important criterion for prenozological diagnostics is justified from the theoretical as well as practical prospective. The classification of prenozological states based on the BA is presented. The experiment features data of 159 children aged 7-10 years. Analyses of the obtained mean functional age (FA) data shows deviation from the calendar age (CA) in all age and gender groups which enables to diagnose prenozological state of elementary school-age children.